UPAYA UNTUK MENINGKATKAN PENGETAHUAN MATERI TITIK BERAT MENGGUNAKAN LKPD MODEL PROJECT BASED LEARNING - Heru Parjono (Jurnal AlphaEuclidEdu, 2023)
Classroom action research in general aims improving the quality of learning for class XI MIA 2 students of SMA Negeri 1 Siantan. Specifically for: (1) Improve mastery of knowledge of heavy point material after using LKPD PjBL model and (2) Knowing the results of the weight point material test after learning using the LKPD PjBL model. The method used is PTK. Data collection techniques and tools with test instruments and observation sheets. The results of the first cycle study showed 69% and cycle II results show 80%. %. The conclusion of the results of the first cycle achievement research is not ideal because it is still below 75% with medium predicate, and a completion percentage of 56% of 36 students. Learning in cycle II reaches 80% with high predicate. Learning in cycle II reaches 80% with high predicate.